High-ceramic-yield precursor to SiC-based ceramic: A hyperbranched polytitaniumcarbosilane bearing self-catalyzing units. Issue 2 (February 2015) - Yu, Zhaoju; Yang, Le; Min, Hao; Zhang, Pei; Liu, Anhua; Riedel, Ralf
Abstract A novel hyperbranched polytitaniumcarbosilane (HPTiCS) was synthesized by a monomer route. The obtained HPTiCS contains dicyclopentadienyl titanium units, which exhibits excellent self-catalytic activation of the dehydrocoupling reaction during its cross-linking process. As a result, the 1200 °C ceramic yield of the pyrolyzed HPTiCS is 32 wt% higher than that of titanium-free hyperbranched hydridopolycarbosilane (HPCS). Compared with titanium-free HPCS-derived SiC, the resulting HPTiCS-derived SiC-based ceramic exhibits a significantly enhanced resistance toward the growth of the in situ formed β-SiC crystals as the matrix phase after being annealed at 1600 °C.